Wittgenstein, medicine and neuropsychiatry - Hélio A.G. Teive; Guilherme Ghizoni Silva; Renato P. Munhoz (Arquivos de Neuro-Psiquiatria)
A historical review is presented of the link between Ludwig Wittgenstein, considered the most important philosopher of the 20th century, and medicine, particularly neurology and psychiatry. Wittgenstein worked as a porter at Guy's Hospital in London, and then as a technician at the Royal Victoria Infirmary in Newcastle. He wrote about his important insights into language, and neuroscience. It has been suggested that he had Asperger syndrome and a possible movement disorder (mannerisms).